OP0230 The effectiveness of zoster vaccine in RA patients subsequently treated with TOFACITINIB. (15th June 2017) - Winthrop, KL; Wouters, A; Choy, EH; Nduaka, C; Biswas, P; Wang, L; Hodge, J; Lazariciu, I; Soma, K; Mojcik, CF; Rigby, WFC
Abstract : Background: Rheumatoid arthritis (RA) patients (pts) are at increased risk of herpes zoster (HZ). The most recent ACR guidelines of 2015 recommend vaccination in pts aged ≥50 years prior to starting biologic DMARDs or tofacitinib, 1 an oral Janus kinase inhibitor for the treatment of RA. Live zoster vaccine (LZV) has shown 70% efficacy in immunocompetent adults aged 50–59 years and 51% efficacy in those aged ≥60 years. 2 We previously reported that pts with RA on background methotrexate who started 3 months of treatment with tofacitinib after LZV had similar varicella zoster virus (VZV)-specific immunity to placebo (PBO) pts, and their VZV immunity at Week 6 post-vaccination was comparable with healthy individuals aged ≥50 years. 3 Objectives: To evaluate the long-term effectiveness of LZV in pts with RA via the incidence of HZ after treatment with tofacitinib for up to 27 months. Methods: Data were analysed from a prior cohort of pts (n=100) given LZV and then randomised 2–3 weeks later to tofacitinib 5 mg twice daily (BID) or PBO for 12 weeks (A3921237 [NCT02147587 ]). At 14 weeks post-vaccination, pts joining the long-term extension (LTE) study ORAL Sequel (NCT00413699 ; study ongoing; database not locked) initiated open-label treatment with tofacitinib 5 or 10 mg BID. The incidence of HZ post-vaccination after tofacitinib exposure up to 27 months (based on an extended follow-up beyond January 2016 data snapshot) was evaluated. Among HZ cases, we analysed measures of VZV-specific immunity with average immunity after LZV. Results: 112 pts were randomised to PBO (n=57) or tofacitinib 5 mg BID (n=55). 100 pts continued to receive tofacitinib in ORAL Sequel. Five cases (not adjudicated) of HZ occurred (#1: 202 days [219 days post-LZV], #2: 267 days [281 days post-LZV], #3: 702 days [748 days post-LZV], #4: 699 days [741 days post-LZV], #5: 446 days [544 days post-LZV] after initiation of tofacitinib. Cases #1, #2, #3 and #4 were monodermatomal; #5 involved 5 dermatomes. All cases resolved with treatment. Cases #1, #4 and #5 had undetectable ELISPOT measures at baseline and Week 6 post-vaccination, indicating a lack of VZV-specific immunity. Cases #2 and #3 responded adequately to vaccination by both immunoglobulin G (IgG) and ELISPOT measures, but had lower than average VZV IgG levels, both at baseline and at Week 6. (Table). Conclusions: LZV prior to treatment with tofacitinib is effective at boosting IgG levels and cell-mediated immunity towards VZV. No pts who developed both strong cell-mediated and humoral immunity against VZV developed HZ. Of the 5 pts who developed HZ, 3 did not have any cell-mediated response and 2 had a low humoral response. References: Singh JA et al. Arthritis Care Res (Hoboken) 2016; 68: 1–25. Hales CM et al. MMWR Morb Mortal Wkly Rep 2014; 63: 729–731. Winthrop K et al. Arthritis Rheumatol 2015; 67: Abstract 12L. Acknowledgements: This study was sponsored by Pfizer Inc. The authors would like to acknowledge Lisa McNeil. Editorial support was provided by K Haines and C Evans of CMC and was funded by Pfizer Inc. Disclosure of Interest: K. Winthrop Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Galapagos, Pfizer Inc, UCB, A. Wouters Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Choy Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Hodge Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, I. Lazariciu Consultant for: Pfizer Inc, Employee of: Quintiles, K. Soma Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Mojcik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. F. Rigby Grant/research support from: Amgen, Pfizer Inc, Roche, Consultant for: Bristol-Myers Squibb, Eli Lilly, Pfizer Inc, Roche